Modified B. G. Prasad socioeconomic scale: 2022 update of India - Sood, Parul; Bindra, Supreet; Singh, Pankajpreet (International Journal Of Community Medicine And Public Health, 2023)
Socioeconomic status (SES) is one of the most important determinants of family’s health as well as access to resources. It is vital to determine the SES of the participant in community-based research for documenting the incidence and prevalence of numerous health related events. The modified BG Prasad SES is one of the most widely used tool to determine the SES of rural and urban population but this scale requires regular update taking into account the inflation and deflation of value of the Rupees as this scale is based on the per capita Income of an individual. It is based on consumer price index (CPI) for industrial workers. The updated version of Modified BG Prasad for year 2022 thus presented.